Individual apparatus results of female all around olympic champions - Pajek, M. (Science of Gymnastics Journal, 2018)
The changes of Code of Points stimulate the rise in exercise difficulty and a drive towards increased specialization of gymnasts. We inspected the performance of all-around medalists at individual apparatus finals to analyze the trends in their efficiency to reach the podium. Data from Olympic games 1952-2016 was included in this retrospective study. In the period form 1952-1984 there were 5 occasions when all-round winners reached 75 to 100% efficiency in reaching the podium at all individual apparatus finals. However overall, there is a clear trend of diminished efficiency of all-around winners to reach the podium at individual finals in the observed period (1952-2016) from the average of 7.7 medals in the first three observed events to 4.3 medals at the last three observed events. Olympic all-around champion efficiency was calculated from sum of all medals won by all-around champions on apparatuses divided by 4. This efficiency has decreased from 91.7% in the first three events to 41.7% in the last three events. In recent events all-around champions still managed to win at least one medal on single apparatuses as there was only one exception to this rule at 2012. It is very much probable that in the future all-around champions will excel further at single apparatus finals; however a huge predominance of all-around champions at apparatus finals cannot be expected any more.